Systemic Reprogramming of Monocytes in Cancer - Kiss, Máté; Caro, Aarushi Audhut; Raes, Geert; Laoui, Damya (Frontiers in Oncology, 2020)
Monocytes influence multiple aspects of tumor progression, including antitumor immunity, angiogenesis and metastasis, primarily by infiltrating tumors and differentiating into tumor-associated macrophages. Emerging evidence suggests that the tumor-induced systemic environment influences the development and phenotype of monocytes before their arrival to the tumor site. As a result, circulating monocytes show functional alterations in cancer, such as the acquisition of immunosuppressive activity and reduced responsiveness to inflammatory stimuli. In this review, we summarize available evidence about cancer-induced changes in monopoiesis and its impact on the abundance and function of monocytes in the periphery. In addition, we describe the phenotypical alterations observed in tumor-educated peripheral blood monocytes and highlight crucial gaps in our knowledge about additional cellular functions that may be affected based on transcriptomic studies. We also highlight emerging therapeutic strategies that aim to reverse cancer-induced changes in monopoiesis and peripheral monocytes to inhibit tumor progression and improve therapy responses. Overall, we suggest that an in-depth understanding of systemic monocyte reprogramming will have implications for cancer immunotherapy and the development of clinical biomarkers.